Does the age matter in acquiring second language? - Diana Oktavia (Journal Of Language Education and Development (JLed), 2020)
It has been being debatable issue for very long time, the early starter verseus late starter in the second language acquisition. Some researchers assumed and found that the early starter can acquire language better than the late starter, because they are in the critical period. While, some researchers found that the late starter can acquire and perform the new language better than the early starter, because they have better ability in understanding some aspects of languages. Therefore, this current paper concerned to find any factors influence someone in acquiring the second language acquisition. This study involved nine International students who are studying in Hungary, they started learning and acquiring Hungarian language when they have passed their critical period. This current study found that the age is not the only main factor in acquiring the language, but there are some other factors, including the society, access to the language, attitude toward language, love, and friendship/relationship.